Krakau Partituren Bachelor- und Masterentwerfen - Hasler, Thomas; Nizic, Ines; Jadric, Mladen; Brnic, Ivica; De Chiffre, Lorenzo; Krenn, Theresa (Schriftenreihe der Fakultät für Architektur und Raumplanung, 2020)
The following publication shows selected projects from the Research Unit Building Construction and Design 1, which were assigned as part of the course Design and Construction. An explanation of the methodology of simultaneous design serves as the introduction to this publication. The teaching material and assignments in the Research Unit Building Construction and Design 1 focus on the important connection between construction and architectural form. The goal of this project assignment was to create a construct in which concepts of space and form combine with spatial and constructive logic to create expressive architecture. In closing, the publication includes didactic reflection on, presentation and graphic depiction of workflow processes. The product of a research trip during the Winter semester 2018/19, "Kraków / Musical Score" applied these methods to plan interventions in Kraków, the European Capital of Culture in 2000, all of which are dedicated to the theme of music. The various themes and typologies change rhythmically and find their architectonic and constructive expression in music schools, concert halls, musical theatres and other musical venues, which serve the city with a rich palette of expressive sound spaces.